Correction: De novo prediction of cross-effect efficiency for magic angle spinning dynamic nuclear polarization. Issue 24 (11th June 2021) - Mentink-Vigier, Frédéric; Barra, Anne-Laure; van Tol, Johan; Hediger, Sabine; Lee, Daniel; De Paëpe, Gaël
Abstract : Correction for ' De novo prediction of cross-effect efficiency for magic angle spinning dynamic nuclear polarization' by Frédéric Mentink-Vigier et al., Phys. Chem. Chem. Phys., 2019, 21, 2166–2176, DOI: ; 10.1039/C8CP06819D .